2018
DOI: 10.1155/2018/6241856
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Chest Compression Quality Measurements by Smartphone Camera

Abstract: Out-of-hospital cardiac arrest (OHCA) is recognized as a global mortality challenge, and digital strategies could contribute to increase the chance of survival. In this paper, we investigate if cardiopulmonary resuscitation (CPR) quality measurement using smartphone video analysis in real-time is feasible for a range of conditions. With the use of a web-connected smartphone application which utilizes the smartphone camera, we detect inactivity and chest compressions and measure chest compression rate with real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
6
0
2
Order By: Relevance
“…We recommend that DACPR training for dispatchers should focus on appropriate repetition (e.g., engaging callers to actively count their compressions out loud). The training could also focus on the directness of the channel (using multiple functions of the smart phone to facilitate DACPR communication, e.g., video call, 34 GPS location, or specific app's 35,36 ) and situation-specific script adherence (e.g., using computer prompts to emphasize important language specific details of the script). Other recommendations include the use of simulation to validate the translation of the DACPR script into different languages, and the use of a metronome to guide the dispatcher on correct compression rates.…”
Section: Discussionmentioning
confidence: 99%
“…We recommend that DACPR training for dispatchers should focus on appropriate repetition (e.g., engaging callers to actively count their compressions out loud). The training could also focus on the directness of the channel (using multiple functions of the smart phone to facilitate DACPR communication, e.g., video call, 34 GPS location, or specific app's 35,36 ) and situation-specific script adherence (e.g., using computer prompts to emphasize important language specific details of the script). Other recommendations include the use of simulation to validate the translation of the DACPR script into different languages, and the use of a metronome to guide the dispatcher on correct compression rates.…”
Section: Discussionmentioning
confidence: 99%
“…Smartphones with the addition of software can be used for physical examination, information communication (e.g., ECGs), performance feedback (e.g., CPR), and consultation (e.g., orthopedic injuries). [190][191][192][193][194][195][196][197][198][199] While promising, these studies lacked follow-up to demonstrate safety with wider implementation. [200][201][202][203][204] Several studies evaluated the quality of patient-reported data (e.g., blood pressure) and concluded that these were reliable means to collect such data.…”
Section: Safety In Emergency Telehealthmentioning
confidence: 99%
“…The accuracy and validation of the TCPRLink app has been demonstrated earlier. 17 The illustration of the application in use is presented in figure 1. By clicking the 'Press to start TCPR Link' button, the application activates the speaker, establishes a telephone connection with the dispatcher, activates the TCPRLink app which captures and analyses the CPR movement via the front facing camera of the smartphone in real time, and simultaneously sends the location and real-time compression data to a web server which is available for the dispatcher (web server: http:// tcprlink.…”
Section: Tcprlink Applicationmentioning
confidence: 99%
“… 13 14 In adherence to these guidelines, an audiovisual smartphone application (TCPRLink) was developed to facilitate high-quality bystander-provided CPR and assist the dispatcher to evaluate the CPR quality in real time. 15 The TCPRLink application utilises the smartphone front camera to detect chest compressions (CC) and displays the CC rate to the bystanders and simultaneously sends the real-time CC rate and the time without compressions via the internet to a monitor that is in front of the dispatcher.…”
Section: Introductionmentioning
confidence: 99%